Coffee Culture's Role In Community Resilience: A Case Study Of Buraidah Speciality Coffee - Maspul, Kurniawan Arif (Journal Health of Indonesian, 2025)
This research investigates the socio-cultural and psychological dimensions of coffee culture in Buraidah, Al Qassim, revealing its pivotal role as both a stimulant and a facilitator of social interaction. The implications of this study extend beyond local contexts, suggesting that coffee culture can stimulate sustainable economic practices while reinforcing community ties. On the other hand, framing coffee as a catalyst for social integration and cultural identity, the research highlights its potential to enhance resilience in communities facing contemporary challenges. Ultimately, this exploration asserts coffee culture’s profound global impact, encouraging recognition of its role in enhancing individual wellness, strengthening social bonds, and promoting economic vitality. Understanding and nurturing coffee culture emerges as a vital pathway toward enriched social interaction and a collective sense of purpose in an increasingly complex world.